Strength variation of pre-strained (transverse compressive) aluminium alloy due to isochronal annealing - Liza, Ranggi (2007)
This thesis deals with strength variation of pre-strained (transverse compression) Al-Mg alloy sheets due to isochronal annealing which is to simulate the conditions of after paint bake cycle of Al-Mg alloy automotive Body-In-White by influenced of pre-straining. The objective of this thesis is to investigate the influences of the varied annealing heat treatment temperatures (175°C, 200°C, and 225°C) and different amount of pre-straining (transverse compression at 10%, 15%, 20% and 25%) which causes the softening behaviour of the material. The materials used in this thesis are Al-Mg alloy sheets of AA1 100, AA5052 and AA5083 which are usually used to build vehicle structure. lOmmx 10mm rectangular piece specimens were prepared to undergo full annealing (300°C for 1 hour) before the compression test at varied percentage and then annealed again at the different assigned temperatures. The second compression is done to obtain the results of the amount of softening at varied temperature and percentage of transverse compression. The results where the softening behaviour were characterized can also be used as guidance to improve the available facilities, thus, helpful reference for future usage in order to achieve the hypotheses result of this thesis.